Music listening in foreign language learning: perceptions, attitudes, and its impact on language anxiety - Kim, Hyun-Ju; Chong, Hyun Ju; Lee, Mihye (Frontiers in Education, 2024)
The present study explored university students' perceptions and attitudes towards music listening in foreign language learning, examining its perceived supportive role in their learning process. In this study, 'music listening in foreign language learning' refers to the practice of incorporating music as a background accompaniment during language study. With 200 participants from various majors, findings indicated that a majority (94.5%) frequently listened to music in general, with a preference for slow ballad, fast dance, and classical music genres for language study. Of these, 142 stated that listening to music played a beneficial role in their foreign language learning, perceiving it not just as a stress-reliever but also a valuable tool enhancing language skills. A significant correlation emerged between music listening and decreased communication apprehension from the Foreign Language Classroom Anxiety Scales (FLCAS). Hierarchical regression highlighted the individual variables like gender, age, and English proficiency as influential factors in foreign language anxiety, while frequent music listening displayed a protective, inverse relationship with such anxiety.The findings suggest foreign language proficiency demands both knowledge and emotional stability, with managing anxiety through informal practices like music listening playing a critical role. This highlights the potential for further pedagogical insights and more detailed subsequent research.